An analysis of stress, burnout, and work commitment among disability support staff in the UK. (December 2015) - Smyth, Emmett; Healy, Olive; Lydon, Sinėad
Highlights: Levels of perceived stress, burnout, and work commitment were examined in disability support workers. Exposure to challenging behaviour was associated with perceived stress and emotional exhaustion. Perceived stress and burnout were associated with work commitment. Frequency and severity of aggressive/destructive behaviour predicted depersonalization. Greater perceived stress was a predictor of depersonalization and emotional exhaustion. Abstract: Previous research has suggested that challenging behaviour emitted by persons with intellectual and developmental disabilities negatively impacts upon the levels of stress and burnout of those who support and care for them. In the current study a sample of disability support workers in the UK ( N  = 138) reported their levels of perceived stress, burnout, and commitment to their work. The relationship between the frequency and severity of aggressive/destructive behaviours to which they were exposed, and these three measures were examined. Results showed that participants scored lower on measures of burnout in the current study than has been reported by similar research studies in the UK and North America. The results revealed an association between challenging behaviours experienced and participants' perceived stress and emotional exhaustion. Perceived stress and burnout were also associated with participants' commitment to their work. Finally, a series of regression analyses identified a number of predictors of emotional exhaustion, depersonalization, and personal accomplishment among disability support workers. The results and their implications for the consideration of disability support worker wellbeing and future research in this area are discussed.